2017
DOI: 10.1002/eap.1491
|View full text |Cite
|
Sign up to set email alerts
|

Increased pollinator habitat enhances cacao fruit set and predator conservation

Abstract: The unique benefits of wild pollinators to the productivity of agricultural crops have become increasingly recognized in recent decades. However, declines in populations of wild pollinator species, largely driven by the conversion of natural habitat to agricultural land and broad-spectrum pesticide use often lead reductions in the provision of pollination services and crop production. With growing evidence that targeted pollinator conservation improves crop yield and/or quality, particularly for pollination sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 87 publications
2
23
0
1
Order By: Relevance
“…The low R. nitida densities in the ‘with cacao husk’ treated plots may be due to the dispersal of R. nitida beetles outside of the plots or due to within‐plot mechanism ( e.g ., unsuitable habitats for R. nitida reproduction and/or survival or increased predation on R. nitida beetles mediated by habitat‐related increases in predator densities). In a concurrent study, we found that in addition to increasing pollination rates, the addition of cacao fruit husks as mulch underneath trees increased the densities of native spider and skink predators (Forbes ). Thus, it is possible that increased native predator densities within the ‘with cacao husk’ treated plots helps to maintain low insect pest densities in the absence of the predaceous O. smaragdina ants.…”
Section: Discussionmentioning
confidence: 89%
“…The low R. nitida densities in the ‘with cacao husk’ treated plots may be due to the dispersal of R. nitida beetles outside of the plots or due to within‐plot mechanism ( e.g ., unsuitable habitats for R. nitida reproduction and/or survival or increased predation on R. nitida beetles mediated by habitat‐related increases in predator densities). In a concurrent study, we found that in addition to increasing pollination rates, the addition of cacao fruit husks as mulch underneath trees increased the densities of native spider and skink predators (Forbes ). Thus, it is possible that increased native predator densities within the ‘with cacao husk’ treated plots helps to maintain low insect pest densities in the absence of the predaceous O. smaragdina ants.…”
Section: Discussionmentioning
confidence: 89%
“…The ecophysiology of pollination and fertilization of cacao beans is manageable by optimized agrocultural practices. Adequate midge breeding sites using cocoa pod and banana pseudostem can improve the insect population and subsequently increase pollination and fertilization [95]. This management practice is envisaged as the way to increase bean yield.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, reducing the dosage would decrease the impact of the contact insecticides on mirid predators leading to a higher amount of cherelles observed after treatments. Weaver ants Oecophylla longinoda and Oecophylla smaragdina have been suggested as key-predators to mirids in cocoa cropping systems in Cameroon (Babin et al, 2010;2011 and Australia (Forbes and Northfield, 2017), respectively. Those predatory ants will less likely be killed by insecticide products that do not contain pyrethroids and will consequently be able to maintain their populations to levels that are able to significantly reduce mirid numbers.…”
Section: Discussionmentioning
confidence: 99%